2015
DOI: 10.17795/jjnpp-20008
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Ferula assafoetida on Muscarinic Receptors of Guinea-Pig Tracheal Smooth Muscle

Abstract: Background: In traditional medicine, asafoetida obtained from the roots of different Ferula assafoetida (F. asafoetida) is used for various therapeutic purposes such as whooping cough, pneumonia and bronchitis in children, as well as asthma. Objectives: In this study, the effect of asafoetida on muscarinic receptors of tracheal smooth muscle, as one possible mechanism responsible for the relaxant effect seen for the plant, was evaluated. Materials and Methods:The effects of three cumulative concentrations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…While the concentration ratio minus one value obtained in the presence of all concentrations of extract was significantly lower than those of atropine. These results also suggested the inhibitory effect of this plant on muscarinic receptors (Khazdair, Boskabady, Kiyanmehr, Hashemzehi, & Iranshahi, ).…”
Section: Resultsmentioning
confidence: 72%
“…While the concentration ratio minus one value obtained in the presence of all concentrations of extract was significantly lower than those of atropine. These results also suggested the inhibitory effect of this plant on muscarinic receptors (Khazdair, Boskabady, Kiyanmehr, Hashemzehi, & Iranshahi, ).…”
Section: Resultsmentioning
confidence: 72%
“…The relaxant effect of aqueous extract of F. assa-foetida (2, 5, and 10 mg/ml) on the smooth muscle of the guinea pig tracheal chain ( in vitro study) was reported [ 95 ]. The relaxant effect of F. assa-foetida extract via inhibitory effect on histamine (H1) receptors, muscarinic receptors, and possible mechanisms for functional antagonistic on tracheal smooth muscle) have been investigated and [ 96 , 97 ] also reviewed [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been also reported that oleo-gum resin of F. asafoetida possesses sedative, expectorant, analgesic, carminative, stimulant, antiperiodic, ant-diabetic, anti-spasmodic, emmenagogue, vermifuge, laxative, anti-inflammatory, contraceptive and anti-epileptic effects 59 . Effects of F. asafoetida on muscarinic receptors and possible mechanisms for functional antagonistic of guinea-pig tracheal smooth muscle have been studied 60 , 61 . The relaxant effect of F. assafoetida on smooth muscles and its possible mechanisms have been reviewed 62 .…”
Section: Neuroprotective Effects Of Medicinal Plantsmentioning
confidence: 99%
“… 59 Effects of F. asafoetida on muscarinic receptors and possible mechanisms for functional antagonistic of guinea-pig tracheal smooth muscle have been studied. 60 , 61 The relaxant effect of F. assafoetida on smooth muscles and its possible mechanisms have been reviewed. 62 In pharmacological and biological studies, the ole-gum- resin of Ferula asafoetida have been revealed to have antioxidant, antiviral, antifungal, anti-diabetic, molluscicidal, antispasmodic and antihypertensive effects.…”
Section: Neuroprotective Effects Of Medicinal Plantsmentioning
confidence: 99%